Optimisation of Immobilisation Condition of ProteaseExtracted from Silver Catfish (Pangasius sutchi) Viscera inCalcium Alginate by using Response Surface Methodology(RSM) / Siti Noorsyarafana Sahimi and Normah Ismail - Sahimi, Siti Noorsyarafana; Ismail, Normah (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Traditionally, enzymes are available both as freeze-dried or powdered form and cannot be recovered back once being used and the animal origin or background sources of the enzyme can raise doubt among the Muslims. Thus, the purpose of this study was to determine the optimum immobilisation condition of protease extracted from silver catfish (Pangasius sutchi) viscera by using response surface methodology. Optimisation of immobilisation condition is important to obtain maximum proteolytic activity thus producing high quality of immobilised enzyme that can be used and recovered for multiple times. In this study, protease from silver catfish viscera has been extracted, partially purified by acetone precipitation method and immobilised in the calcium alginate beads. Sodium alginate and calcium chloride in the range of 1-5% w/v and 0.1 - 0.5 M respectively were used for the optimisation purpose. The proteolytic activity of the protease in the alginate beads was measured as a response to the independent variables by using casein as a substrate. The highest actual and predicted proteolytic activities were 674.77 CDU/mg and 639.26 CDU/mg respectively, using sodium alginate and calcium chloride solution concentrations at 3.00% (w/v) and 0.30 M, respectively. For the experimental feasibilities, the optimum conditions that were feasible to be carried out were with sodium alginate of 2.99% (w/v) and 0.30 M calcium chloride solution. There was no significant difference (p > 0.05) found between the predicted (638.19 CDU/mg) and verified (699.82 CDU/mg) values. Thus, indicating that the model was significant and can be used to produce the immobilised protease under the optimum condition